Counterspaces of Resistance: Peter Carey’s Bliss - Barbara Klonowska (Anglica. An International Journal of English Studies)
The article discusses how Peter Carey’s 1980 novel Bliss constructs and examines various counterspaces both in and beyond the text. First, it shows how the plot juxtaposes the consumerist middle-class suburban model of life with an alternative lifestyle, presenting the attractions and limitations of both, yet preferring rather the latter. Secondly, at the level of literary convention, the text activates the strategies of comic social realism only to juxtapose them with elements of fantasy, fairy tale and myth, thus undermining the representational powers of the former and hinting at other possibilities of representation. Finally, the film adaptation of the novel shows how even rebellious or critical texts may become ‘domesticated’ or absorbed by the dominating logic of cultural production, thus once again demonstrating the ambivalent position of works of art in general, and this novel in particular. The article argues that the ambivalence engrained in the text is an intrinsic feature, not only of Australian culture or heterotopias but of most cultural products and practices inevitably entangled in the double logic of conforming and resistance.